2011
DOI: 10.3109/00016357.2011.600706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in trabecular alveolar bone during growth using conventional panoramic radiographs

Abstract: Objective. To assess changes of the alveolar trabecular bone during growth using panoramic radiographs and to detect possible differences in trabecular bone patterns when comparing individuals of various ages and genders. Materials and methods. Conventional panoramic radiographs of 18 young (eight females, 10 males) and 21 adult (12 females, nine males) subjects were taken at 2 years (T1) and 10 years (T2) after the end of orthodontic treatment. At T1, mean ages were 15.6 ± 0.9 years and 31.3 ± 9.7 years in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…But patients’ gender, race and age can influence bone metabolism. 25 Kiliaridis et al 10 conducted a research to evaluate changes in alveolar bone trabeculation during growth using the same three-scale visual analysis on PRs taken two and ten years following orthodontic treatment and to discover possible differences in patterns of trabeculation in patients of various genders and ages. They found that denser trabeculation in the alveolar bone seemed to be related to age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But patients’ gender, race and age can influence bone metabolism. 25 Kiliaridis et al 10 conducted a research to evaluate changes in alveolar bone trabeculation during growth using the same three-scale visual analysis on PRs taken two and ten years following orthodontic treatment and to discover possible differences in patterns of trabeculation in patients of various genders and ages. They found that denser trabeculation in the alveolar bone seemed to be related to age.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A three-scale visual analysis was applied in our study, which has been shown to evaluate trabeculation on PRs in previous studies. 10,26 It has already been proved that PRs can be as useful as periapical radiographs in assessing trabecular pattern. 26 Although CBCT and other advanced 3D modalities of radiography are more accurate and provide more details, taking them routinely for orthodontic purposes seems unnecessary and uncommon because of their cost and lack of availability in all the oral and maxillofacial radiology centers and also their significant radiation doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandibular trabecular bone becomes denser in the jaws from puberty to middle age. 13 With aging, alveolar trabecular bone becomes sparser in most women. 11 Current knowledge regarding the effects of osteoporosis or osteopenia on periodontal disease and alveolar bone loss is inconclusive, 14,15 but it is known that the thickness of the trabeculae, the spacing between the trabeculae, and trabecular connectivity are altered in patients with osteoporosis compared with those without.…”
mentioning
confidence: 99%